2009
DOI: 10.17660/actahortic.2009.812.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Source, Carbon Concentration and Culture Conditions on in Vitro Rooting of Pinus Pinea L. Microshoots

Abstract: Clonal propagation via adventitious bud stimulation from cotyledon explants has been reported before in stone pine (Pinus pinea L.), however the number of rooted shoots had low frequency and short growth span. Therefore the main objective of the present work was to increase the number and quality of roots per shoot in order to ensure the survival and growth of a great number of plants in the acclimation phase. To achieve this, different combinations of carbon source (sucrose or glucose) at different concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The elongated microshoots (2 cm long separated from any browning tissues) were then transferred to modified WPM root induction medium with half concentration of macronutrients and 5.35 lM of naphthaleneacetic acid (NAA), where they remained for 2 weeks. Culture conditions were 19°C in darkness during the first week and 19°C with 16 h photoperiod during the second week (Zavattieri et al 2009). Following the root induction treatment, the shoots were transferred to root expression medium consisting of modified WPM (half concentration of macronutrients) PGR-free medium.…”
Section: Treatments With Naphthaleneacetic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The elongated microshoots (2 cm long separated from any browning tissues) were then transferred to modified WPM root induction medium with half concentration of macronutrients and 5.35 lM of naphthaleneacetic acid (NAA), where they remained for 2 weeks. Culture conditions were 19°C in darkness during the first week and 19°C with 16 h photoperiod during the second week (Zavattieri et al 2009). Following the root induction treatment, the shoots were transferred to root expression medium consisting of modified WPM (half concentration of macronutrients) PGR-free medium.…”
Section: Treatments With Naphthaleneacetic Acidmentioning
confidence: 99%
“…Rooted shoots were washed carefully in water to eliminate residual medium and planted in pots filled with non sterile substrate mix of perlite:vermiculite:peat moss (1:1:1) (v/v) (Zavattieri et al 2009). We used a special culture chamber equipped with light and dry mist system to provide high relative humidity, and therefore it was not necessary to cover the plantlets.…”
Section: Rooting Of Plantlets In Various Substrates and Acclimatizationmentioning
confidence: 99%
“…However, other carbohydrates such as glucose and fructose have been also used to improve organogenesis (Faye et al 1989;Ordás et al 1999;Zavattieri et al 2009). The exogenous sucrose (in the presence or absence of auxin) is beneficial for the rooting of most herbaceous and woody plants (Haissig 1982).…”
Section: Carbohydratesmentioning
confidence: 99%
“…Zavattieri et al (2009) made a direct comparison between different carbon sources (sucrose or glucose at different concentrations) for the induction and expression phases of the adventitious roots in microshoots of Pinus pinaea. An increased number of roots per shoot and an accelerated root formation were consistently obtained using glucose.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Inoculation with specific fungi can enhance pine root formation and/or subsequent root branching of cuttings ( Normand et al , 1996 ; Karabaghli et al , 1998 ; Niemi et al , 2000 ). Some research results demonstrated the potential use of ECM fungi in the vegetative propagation of conifers ( Gay, 1990 ; Niemi et al , 2005 ) and during in vitro rooting of pine shoots ( Zavattieri et al , 2009 ; Ragonezi et al , 20010a). Inoculations enhanced plant performance and contributed to alleviation of stress related with acclimation in a nursery and the subsequent growth in the field.…”
Section: Introductionmentioning
confidence: 99%